Promotional Media Design for Joompo.id Based on the Omen Character Targeting Generation Z Audiences - Alyaa Parisya Putri; Asidigisianti Surya Patria; Nanda Nini Anggalih (fakultas Desain Komunikasi Visual, 2025)
This study aims to design promotional media for Joompo.id by highlighting the phenomenon of “pemuda jompo” as the main visual concept to attract younger audiences. This phenomenon describes a young generation that is active yet easily tired, making humor about fatigue part of their daily expression. This potential is translated through the character Omen, which serves as the center of visual storytelling across promotional materials. The research uses a qualitative descriptive approach through observation of competitors’ social media and informal interviews with audiences to understand visual preferences and relevant communication styles. The SWOT analysis technique was applied to identify factors that influence the effectiveness of promotional media design. The findings show that the use of humorous characters and consistency in visual elements can increase content appeal, strengthen brand messages, and build emotional connections with audiences. The resulting promotional media is not only informative but also entertaining and relevant to the experiences of young people, making it more effective in enhancing brand appeal